Early cardiology assessment and intervention reduces mortality following myocardial injury after non-cardiac surgery (MINS) - Hua, Alina; Pattenden, Holly; Leung, Maria; Davies, Simon; George, David A.; Raubenheimer, Hilgardt; Niwaz, Zakiyah; Lim, Eric (Journal of Thoracic Disease; Vol 8, No 5 (May 01, 2016): Journal of Thoracic Disease, 2016)
Background: Myocardial injury after non-cardiac surgery (MINS) is defined as troponin elevation of ≥0.03 ng/mL associated with 3.87-fold increase in early mortality. We sought to determine the impact of cardiology intervention on mortality in patients who developed MINS after general thoracic surgery. Methods: A retrospective review was performed in patients over 5 years. Troponin was routinely measured and levels ≥0.04 ng/mL classified as positive. Data acquisition and mortality status was obtained via medical records and NHS tracing systems. Thirty-day mortality was compared on MINS cohort using Fisher’s exact square testing and logistic regression analysis. Results: Troponin levels were measured in 491 (96%) of 511 patients. Eighty (16%) patients fulfilled the MINS criteria. Sixty-one (76%) received early cardiology consult and “myocardial infarction” stated in four (5%) patients. Risk assessment (for AMI) was undertaken; 20 (25%) patients were commenced on aspirin, four (5%) on β-blockers and one (1%) underwent percutaneous coronary intervention. Forty-nine (61%) patients received primary risk factor modifications and 26 (33%) had outpatient follow-up. There were no significant differences in the proportion of patients who died within 30 days post-operatively in the MINS group of 2.6% compared to the non-MINS group of 1.6% (P=0.625). The odds ratio for 30-day mortality in the MINS group was 1.69 (95% CI: 0.34 to 8.57, P=0.522). Conclusions: MINS is common after general thoracic surgery. Early cardiology intervention reduced the expected hazard ratio of early death from 3.87 to an odds ratio of 1.69 with no significant difference in 30-day mortality for patients who developed MINS.